Investigating of Hard Turning of Automotive Gears with Polycrystalline Copper Nitride (PCBN) Tools as a Substitute for Grinding - Aadesh Yadav; Mr. Dinesh Dubey (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
A traditional machining process, grinding, is used for finishing of hardened automotive gears with complex shapes and forms. The main limitations associated with the grinding process for such type of components are multiple setups, low productivity, less flexibility, high equipment cost, high production cost, and environmental issues related to disposal of used up coolant and grinding dust. In view of such limitations, an alternate machining method hard turning is studied in this article for finishing of the gears. The gears material is 20Mn5Cr5 steel was attained through heat treatment. In these experiments, we were conducted with PCBN tools. The CNC turning centre was used for conducting hard turning. The machining parameters: feed rate (f), depth of cut and cutting speed (vc) to be taken on response attributes: surface roughness and the tool wear. Taguchi DOE, ANOVA, and S/N ratio methods have been applied for optimization. In this study, the roughness of surface and accuracy of quality performance characteristics such as cylindricity, circularity, and straightness obtained in both the processes (hard turning and grinding) were compared. An economic analysis has been conducted for evaluating the potential of hard turning to replace grinding for short machining length components. As the result, feed rate (61%) and depth of cut (36%) highly affects the surface roughness but the cutting speed was insignificant parameter with contribution of (<2 %). The tool wear was affected most by cutting speed with a contribution of 78%. In this paper, it reported that hard turning is an alternate machining technology to cylindrical grinding in machining of hardened automotive gears using a PCBN tool on a modern CNC turning centre.